Nurturing genius: the childhood and youth of Kelvin and Maxwell - Lekner, John (New Zealand Science Review, 2012)
​William Thomson and James Clerk Maxwell, nineteenth century natural philosophers, were friends and colleagues (Thomson was Maxwell’s senior by seven years). This historical note gives a description of their early lives, with emphasis on the influence of their fathers and of Cambridge on their development.Recent research on electrostatics got me into working contact with the early contributions of James Clerk Maxwell and William Thomson (later Baron Kelvin of Largs, and usually referred to as Kelvin). I read their biographies, and was struck by the remarkable similarities in their childhood and youth. Both were Scots, both lost their mothers at an early age, both had fathers who nurtured them intellectually and were ambitious for their career.This note is mainly about William’s and James’ childhood and youth, and comes to a natural stop at their respective completions of the Cambridge Tripos examination. Only a brief cata-logue of their later careers is given. Some of their electrostatic researches are discussed in my Author’s Note at the end.